TATALAKSANA SEORANG PASIEN KRISIS TIROID DENGAN COVID 19 - I Made Dedy Kusnawan (Jurnal Medika Hutama, 2024)
Thyrotoxic crisis or thyroid storm is an acute, life threatening complication of hyperthyroidism. It comes with sudden multisystem involvement. Thyroid hormones affects all organ system, can causes increase of metabolic rate, heart rate, ventricle contractility, gastrointestinal motility, muscle, and nervous system excitability. Various factors can trigger thyroid storm in thyrotoxicosis such as trauma, surgery, pulmonary embolism, myocardial infarction, cerebrovascular disorders, infection, diabetic ketoacidosis, and toxemia gravidarum, and nonadherence in taking anti thyroid drugs. Thyroid storm estimated incidence 0.2 per 100.000 per year. The diagnostic strategy for thyroid storms may take consideration from BurchWartofsky scoring system. Thyroid storm need immediate and accurate management including specific therapy with antithyroid, betablocker, iodine, glucucorticoid, and also supportive treatment. A 45 years old female presents with the chief complaint of shortness of breath and palpitation, fever and cough, the patient is diagnosed with thyroid crisis caused by Graves’ disease and also confirm severe covid 19 infection. The patient showed good response with therapy.